Molecular and immunological heterogeneity of eosinophilic esophagitis: Insights and subtyping - Eric Twum; Ancha Baranova; Aman Ullah (PLoS ONE, 2026)
Background Eosinophilic esophagitis (EoE) and its related subtypes—such as EoE-like esophagitis, lymphocytic esophagitis, and nonspecific esophagitis—pose significant diagnostic challenges due to overlapping clinical, histological, and endoscopic features. Although conventional EoE is well-characterized as a Th2-mediated disorder, the molecular and immunological drivers for its subtypes are poorly understood. We aimed to elucidate the unique molecular signatures underlying these esophageal inflammatory conditions, with the goal of refining disease classification and paving way to targeted therapeutic approaches. Methods We performed an integrative multi-omics analysis incorporating differential gene expression profiling, weighted gene co-expression network analysis (WGCNA), functional enrichment studies, and machine-learning algorithms to identify molecular hallmarks that differentiate EoE from its subtypes. After examining subtype specific alteration in immune and metabolic pathways, novel biomarkers and regulatory mechanisms were uncovered. Results Conventional EoE exhibited a distinct upregulation of periostin ( POSTN ), reinforcing extracellular matrix remodeling as its primary pathogenic mechanism. We identified DNAH11 as a key player in epithelial turnover and esophageal dysmotility, revealing its previously unrecognized role in EoE pathogenesis. Suppressed zinc-related pathways ( MT1X, MT1F, MT2A ) suggest epithelial barrier dysfunction, with differential zinc transporter expression ( SLC39A1, SLC39A2 ) indicating disruptions in zinc homeostasis, which may have therapeutic implications. Additionally, aberrant CDX2 expression linked to methyl-CpG binding proteins suggests an epigenetic contribution to esophageal epithelial remodeling, hinting at metaplasia-like processes in chronic EoE. In contrast, EoE-like esophagitis was primarily immune-driven, marked by CXCR3 ligand activation ( CXCL9, CXCL10, CXCL11 ) and immunoglobulin complex enrichment, indicating systemic immune dysregulation and a potential precursor state to conventional EoE. Lymphocytic esophagitis demonstrated unique signature of metabolic dysfunction, with downregulation of oxidative phosphorylation genes ( NDUFB2, ATP5F1B ) and enrichment of neuro-immune signaling pathways, pointing at interplay between mitochondrial impairment and esophageal sensory dysfunction. A robust interferon-mediated immune response ( STAT1, IRF1 and CXCL10 ) further differentiated the latter subtype from Th2-driven conventional EoE. Nonspecific esophagitis exhibited a dominant humoral immune response, enriched for immunoglobulin-related pathways, suggestive of a B-cell-driven inflammatory mechanism distinct from the T-cell-dominated responses of other EoE subtypes. Conclusions This study unveils novel molecular and immunological distinctions between conventional EoE and its subtypes. We propose that EoE-like esophagitis represents an early immune-activated phase, while lymphocytic and nonspecific esophagitis exhibit distinct metabolic and humoral immune dysregulations, respectively. Key biomarkers, POSTN, DNAH11, CDX2 , and zinc transporters, offer critical insights for improving diagnostic criteria and guiding therapeutic approaches. These findings highlight the importance of subtype-specific therapeutic interventions and warrant longitudinal studies to map disease trajectories and therapeutic responses across EoE and its variants.